2017
DOI: 10.1111/ajo.12648
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of induction of labour regimes for termination of pregnancy, with and without mifepristone, from 20 to 41 weeks gestation

Abstract: This study supports the hypothesis that in pregnancies greater than 20 weeks, the duration of labour and length of admission are reduced when induction of labour for termination of pregnancy is preceded by treatment with mifepristone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Placental location and delayed uterine evacuation were not reported. A more recent Australian cohort study with a broader MTOP inclusion criteria but more comparable median gestational age (22 weeks) within its similarly protocolised mifepristone arm reported equivalent rates of EUA/MROP at 16% but did not include placenta location, prior CS status, rates of PPH or blood transfusion 4 . Delayed uterine evacuation for retained products of conception is not a commonly reported outcome in any of the literature reviewed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Placental location and delayed uterine evacuation were not reported. A more recent Australian cohort study with a broader MTOP inclusion criteria but more comparable median gestational age (22 weeks) within its similarly protocolised mifepristone arm reported equivalent rates of EUA/MROP at 16% but did not include placenta location, prior CS status, rates of PPH or blood transfusion 4 . Delayed uterine evacuation for retained products of conception is not a commonly reported outcome in any of the literature reviewed.…”
Section: Discussionmentioning
confidence: 93%
“…The selection of this study cohort demonstrates that MTOP at or beyond 20 weeks' gestation is most commonly performed for a fetal reported equivalent rates of EUA/MROP at 16% but did not include placenta location, prior CS status, rates of PPH or blood transfusion. 4 Delayed uterine evacuation for retained products of conception is not a commonly reported outcome in any of the literature reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2007 retrospective study that compared mifepristone and misoprostol with misoprostol alone (with a variety of doses) in fetal death found a reduction in time to delivery in the mifepristone group only among those with gestational ages between 21–25 weeks. 13 In their retrospective cohort study, Fyfe and Murray 14 report a shorter duration of labor with the use of mifepristone before induction after 20 weeks of gestation, although it should be noted that only 20% of patients in the mifepristone treatment group had experienced a fetal death before induction. In addition to this, a nonblinded trial conducted in Nepal showed that the use of mifepristone after a fetal death from 20 weeks of gestation onward decreased the dose of misoprostol required, but not the total time from commencement of misoprostol to delivery.…”
Section: Discussionmentioning
confidence: 98%